CAMPHORQUINONE AS A PHOTOINITIATOR IN THE POLYMERIZATION OF2-HYDROXYETHYL METHACRYLATE IN AQUEOUS SOLUTION:A KINETIC STUDY - Iqbal Ahmad et al (Baqai Journal of Health Sciences)
The photoinitiated polymerization of 2-hydroxyethyl methacrylate (HEMA) (1–3 M) using camphorquinone (CQ) / triethanolamine (TEOHA) system has been studied in the pH range 6.0–9.0. The kinetics of the reaction has been evaluated during the initial stages causing about 5% HEMA conversion to avoid the effects of any variation in the volume of the solution. The change in the concentration of HEMA during polymerization has been determined by a UV spectrometric method at 208 nm with a precision of ±3%. The apparent first-order rate constants (kobs) for the polymerization of HEMA by CQ in the presence of 0.01 M TEOHA, carried out up to 100 s, range from 3.35–7.78 (1 M), 2.72–6.78 (2 M) and 2.33–5.89×10–4 s –1 (3 M). The second-order rate constants for the interaction of TEOHA radicals with HEMA (1–3 M) range from 2.33–7.78×10–2 M–1 s –1 at pH 6.0–9.0 indicating an increase in the reactivity of TEOHA radicals with an increase in the pH of the solution. There is a linear relation between kobs (1–3 M HEMA) and inverse of solution viscosity suggesting the quenching of CQ excited state with an increase in the viscosity of the medium